2015
DOI: 10.1016/j.jchemneu.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Organization of cholinergic, catecholaminergic, serotonergic and orexinergic nuclei in three strepsirrhine primates: Galago demidoff , Perodicticus potto and Lemur catta

Abstract: The nuclear organization of the cholinergic, catecholaminergic, serotonergic and orexinergic systems in the brains of three species of strepsirrhine primates is presented. We aimed to investigate the nuclear complement of these neural systems in comparison to those of simian primates, megachiropterans and other mammalian species. The brains were coronally sectioned and immunohistochemically stained with antibodies against choline acetyltransferase, tyrosine hydroxylase, serotonin and orexin-A. The nuclei ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 50 publications
7
45
1
Order By: Relevance
“…Our results revealed that A8, A9, and A10 dopaminergic nuclei in A. planirostris are similar to the patterns described in other mammals, suggesting that these nuclei have strong phylogenetical stability among mammalian species (Calvey et al, 2015a;Calvey et al, 2015b;Calvey et al, 2016). On the other hand, our study demonstrated the occurrence of unique anatomical features in bats for the first time, such as the tSN and a conspicuous SNR.…”
Section: Retrorubral Field -A8supporting
confidence: 85%
“…Our results revealed that A8, A9, and A10 dopaminergic nuclei in A. planirostris are similar to the patterns described in other mammals, suggesting that these nuclei have strong phylogenetical stability among mammalian species (Calvey et al, 2015a;Calvey et al, 2015b;Calvey et al, 2016). On the other hand, our study demonstrated the occurrence of unique anatomical features in bats for the first time, such as the tSN and a conspicuous SNR.…”
Section: Retrorubral Field -A8supporting
confidence: 85%
“…More caudally, large multipolar ChAT-ir neurons were located in the striatum of the miniature pig similar to other mammals (Sofroniew et al, 1982; Armstrong et al, 1983; Mesulam et al, 1984; Satoh and Fibiger, 1985; Mufson and Cunningham, 1988; Mufson et al, 1989; Woolf, 1991; Geula et al, 1993; Varga et al, 2003; Maseko et al, 2007; Bhagwandin et al, 2008; Limacher et al, 2008; Gravett et al, 2009; Bux et al, 2010; Kruger et al, 2010; Pieters et al, 2010; Bajo et al, 2014; Patzke et al, 2014; Calvey et al, 2015a, 2015b, 2016; Dell et al, 2010, 2016a, 2016b, 2016c). The major source of cholinergic striatal innervation is the large aspiny interneurons that comprise 1% of striatal neurons (Woolf and Butcher, 1981; Graveland and DiFiglia, 1985), which regulate intrastriatal local circuit activity (Galarraga et al, 1999; Koós and Tepper, 2002).…”
Section: Discussionmentioning
confidence: 58%
“…The olfactory tubercle of the miniature pig contained ChAT-ir neurons and fibers as described in other mammals (McGeer et al, 1982; Armstrong et al, 1983; Wahle and Meyer, 1986; Woolf, 1991; Varga et al, 2003; Maseko et al., 2007; Bhagwandin et al, 2008; Limacher et al, 2008; Gravett et al, 2009; Bux et al, 2010; Kruger et al, 2010; Pieters et al, 2010; Patzke et al, 2014; Calvey et al, 2015a, 2015b, 2016; Dell et al, 2010, 2016a, 2016b, 2016c). More caudally, large multipolar ChAT-ir neurons were located in the striatum of the miniature pig similar to other mammals (Sofroniew et al, 1982; Armstrong et al, 1983; Mesulam et al, 1984; Satoh and Fibiger, 1985; Mufson and Cunningham, 1988; Mufson et al, 1989; Woolf, 1991; Geula et al, 1993; Varga et al, 2003; Maseko et al, 2007; Bhagwandin et al, 2008; Limacher et al, 2008; Gravett et al, 2009; Bux et al, 2010; Kruger et al, 2010; Pieters et al, 2010; Bajo et al, 2014; Patzke et al, 2014; Calvey et al, 2015a, 2015b, 2016; Dell et al, 2010, 2016a, 2016b, 2016c).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations